Pengaruh Gaya Kepemimpinan Demokratis, Motivasi dan Work-Life Balance Terhadap Kinerja di Taman Wisata Pendidikan Purbasari Pancuran Mas - Bintang Putra Fauzi; Alfato Yusnar Kharismasyah; Suyoto; Maulida Nurul Innayah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Democratic Leadership, Motivation, and Work-life Balance on Employee Performance at Purbasari Pancuran Mas Educational Tourism Park. Data were obtained from 108 respondents through questionnaires, and processed with the help of Smart PLS and multiple linear regression analysis. The research findings prove that democratic leadership and work-life balance positively and significantly impact employee performance. However, motivation has no significant effect on performance. This study reveals the importance of leadership style and work-life balance in improving employee performance, while motivation due to other unidentified factors. The company is advised to strengthen the implementation of democratic leadership and programs supporting work-life balance, while reevaluating its approach to employee motivation to identify other factors that may affect performance.